"A Social Movement in Fact": La Raza and El Plan de Delano. Issue 1 (1st January 2020) - Izaguirre, José G.
ABSTRACT: This essay revisits the rhetoric of El Plan de Delano, a pivotal document in the farm workers movement and the broader Chican@ movement. Composed and circulated during their peregrinación from Delano to Sacramento, California in 1966, the manifesto stretched the topography of race in the 1960s, both geographically and bodily, as it publicized the farm workers' struggle during their wage-strike. My reading of the visual and verbal rhetorics of the pamphlet of El Plan de Delano surfaces race as an energizing topos . I show how El Plan de Delano (re)fashioned a racial identity for farm workers and parlayed that identity in its appeals.